Design and analysis of integrated paper based biochip with microheater for lamp using viral mimicking nano particles - Jeroish Zachariah, Ezhilnavaroji (2022)
A virus is a sub-microscopic infectious organism that causes diseases to humans, animals, and plants resulting in morbidity and may cause mortality. Several techniques, including antibodies, antigens, and RNA, can be used to identify viral infections. However, RNA and antigen detection modalities are preferred to diagnose an active infection. Hence, the requirement of point-of-care tests (POCT) in detecting RNA and antigen is vast, whereas fewer techniques are available due to the requirement of complex structures and methodologies. Moreover, the filtration of viral samples from the blood is a tedious process. The commercialization of paper-based chips in the field of RNA detection holdups due to the inadequate research in the integration of paper-based chips with the techniques adapted for viral RNA detection. Since the amplification occurs at elevated temperatures, certain microheaters are employed, But the microheaters are either costlier for reuse or inexpensive for disposal. For large-scale disposable applications, sputtering or PVD fabrication techniques is time-consuming and increases the workforce. The integration of paper chips with the reusable microheater for loop-medicated isothermal amplification (LAMP) technology is crucial for developing rapid and easy-to-use hand-held point-of-care (POC) diagnosis. By considering all these concerns, we have developed a paper chip for effective filtration of viral particles from the sample and integrated it with a reusable microheater to provide the necessary temperature to initiate the LAMP assay. In this research, lateral and vertical flow paper chips were fabricated using a laser printer and manual cutting, and the filtration efficiency was analyzed using microspheres. The hydrophobic barriers are generated by sandwiching the paper chip between the polyethylene terephthalate (PET) and the glass slide. The porous nature of the filter paper filters the particles in the sample. Similarly, the printed circuit board (PCB) based microheater was fabricated using the wet etching technique and analyzed the thermal characteristics. The results of the paper chip convey that the lateral flow paper chip was inefficient due to PET encapsulation. Still, the vertical flow paper chip with grade 4 inlet and outlet filters 98.57% of unnecessary particles from the sample within 5 sec. Moreover, the wastage of chips can be reduced by reusing the bottom glass slide with proper sterilization. The design analysis of the microheater reveals that the meander configuration outperforms other designs with the thermal difference of only ~8℃ and the power consumption of 1.79 W. Also, the microheater strip width of 1.75mm enhances productivity. In addition, the fabricated microheater with a heat spreader has a thermal difference of only <5℃ when compared with ~10℃ in a microheater without a heat spreader. The developed microheater was stable for over 6 months at room temperature and 10 days in water when encapsulated with PET. As a result, it has a long shelf life and can handle wet biological samples. Moreover, the microheater integrated with paper chip effectively transfers the heat with a temperature difference of 0.5℃. Thus paper chip integrated microheater can pave the way for several applications like lab-on-chip devices, POC assays, rapid nucleic acid amplification tests, cell cultures, and biomolecular research. In the future, the developed paper-based biochip will be tested for real-time biological samples to detect different viral infections.